Unity - Bowden, Oliver (Assassin's creed ;, 2014)
The magnificent city of Paris sees the dawn of the French Revolution. The cobblestone streets run red with blood as the people rise against the oppressive aristocracy. But revolutionary justice comes at a high price...At a time when the divide between the rich and poor is at its most extreme, and a nation is tearing itself apart, a young man and woman fight to avenge all they have lost. Soon Arno and Elise are drawn into the centuries-old battle between the Assassins and the Templars - a world with dangers more deadly than they could ever have imagined.